Development and Delivery Systems of mRNA Vaccines - Liang, Yongjun; Huang, Liping; Liu, Tiancai (Frontiers in Bioengineering and Biotechnology, 2021)
Since the outbreak of SARS-CoV-2, mRNA vaccine development has undergone a tremendous drive within the pharmaceutical field. In recent years, great progress has been made into mRNA vaccine development, especially in individualized tumor vaccines. mRNA vaccines are a promising approach as the production process is simple, safety profiles are better than those of DNA vaccines, and mRNA-encoded antigens are readily expressed in cells. However, mRNA vaccines also possess some inherent limitations. While side effects such as allergy, renal failure, heart failure, and infarction remain a risk, the vaccine mRNA may also be degraded quickly after administration or cause cytokine storms. This is a substantial challenge for mRNA delivery. However, appropriate carriers can avoid degradation and enhance immune responses, effector presentation, biocompatibility and biosafety. To understand the development and research status of mRNA vaccines, this review focuses on analysis of molecular design, delivery systems and clinical trials of mRNA vaccines, thus highlighting the route for wider development and further clinical trials of mRNA vaccines.